The Effectiveness of Ladder Climbing Games on The Knowledge, Attitude, and Practice of Sorting Waste - Kasjono, Heru Subaris; Suwerda, Bambang; Yushananta, Prayudhy; Lestari, Novia (JURNAL INFO KESEHATAN, 2023)
Students' environmental knowledge is strongly related to environmental attitudes and behavior changes, which impact environmental sustainability. Game media is one of the student environmental learning methods. The study aims to evaluate two types of games (Ladder climbing and Trash trees) to increase elementary school students' knowledge, attitudes, and practices (KAP) in waste sorting. The study used a non-equivalent control group design involving 156 elementary school students in grades 4 and 5. All participants were grouped into ladder climbing games/LCG (n=156) and trash trees/TTG (n=156), then an assessment of knowledge, attitude, and practice (KAP) before and after the trial. All data were analyzed with statistical software (Alpha=0.05), with the Wilcoxon and Mann-Whitney tests. The N-Gain scores test is also applied to get the effectiveness value. The study found that most participants were aged 10 and 11 years (88.8%), and there were more female students (55.2%) than males. LCG intervention improves KAP (135.45%, 47.71%, and 92.59%) more than TTG (54.39%, 21.95%, and 54.51%). Significantly, there were differences in KAP values before and after the intervention and between the two types of intervention (p-value <0.05). Study has also found that the LCG method is more effective than the TTG (N-Gain score > 70%). The study has proven that the game method (LCG and TTG) can improve students' KAP in waste sorting. However, the LCG method is more effective than the TTG. The game method is a wise choice to apply to elementary school education so that it is expected to shape environmental behavior.